The cinema forum as a pedagogical tool to analyze the social representation of the teacher in the cinematographic discourse - Liliana Marcela Marentes Rodríguez (Corporación Universitaria Minuto de Dios, 2009)
This article is the product of research and implementation of the group of graduates from the faculty of education Uniminuto entitled "El cine foro como herramienta pedagógica para analizar la representación social del maestro". In this sense, the article briefly displays the presentation of the project and the various theoretical and legal bases around the cine-foro as a pedagogical resource that permits to analyze the different representations of teacher. Consequently, these theoretical references (the projection of films and forums from a semiotic analysis of each study as the social context and social representation of teacher), are the result of the integration of mass media in a pedagogical context and it is taken the cine-foro as a pedagogical resource. That permits to think about the social representation that students have about the teacher.